Extreme-Intensity Laser–Matter Interactions and the Emergence of Strong-Field Quantum Electrodynamics in the Petawatt Era - Luca Romano (Emerging Frontiers Library for The American Journal of Applied Sciences, 2026)
The rapid evolution of ultra-high-power laser technology over the past two decades has fundamentally transformed the experimental and theoretical landscape of high-field physics. The realization of petawatt-class and multi-petawatt laser systems has enabled laboratory access to electromagnetic field strengths approaching, and in some regimes exceeding, those naturally occurring in extreme astrophysical environments. This technological leap has catalyzed the emergence of strong-field quantum electrodynamics as an experimentally accessible domain, where radiation reaction, nonlinear Compton scattering, Breit–Wheeler pair production, and quantum electrodynamic cascades play dominant roles in laser–matter interactions (Danson et al., 2015; Di Piazza et al., 2012). Recent demonstrations of laser intensities surpassing twenty-three orders of magnitude in watts per square centimeter have further narrowed the gap between theoretical predictions formulated in the mid-twentieth century and their direct empirical validation (Yoon et al., 2021). Within this context, the present article develops a comprehensive and critical examination of extreme-intensity laser–matter interactions grounded strictly in the provided literature corpus. The analysis integrates historical developments in laser science, foundational quantum electrodynamics in strong fields, and contemporary experimental and numerical studies of radiation reaction and electron–positron plasma formation. Rather than offering a cursory overview, the article elaborates each concept through extensive theoretical background, scholarly debate, and critical interpretation, emphasizing unresolved tensions between classical, semiclassical, and fully quantum descriptions. Particular attention is devoted to the role of laser-driven particle accelerators, plasma mirrors, and laser–beam collider geometries in enabling experimentally feasible access to nonperturbative regimes of quantum electrodynamics (Bell and Kirk, 2008; Vincenti, 2019; Magnusson et al., 2019). The results section interprets reported findings as emergent patterns within the literature, while the discussion situates these findings within broader debates on the limits of current models, experimental constraints, and the future trajectory toward exawatt-class facilities. By synthesizing advances in laser technology with developments in strong-field theory, this article aims to provide a publication-ready, deeply analytical contribution to the understanding of how extreme light–matter interactions redefine both plasma physics and fundamental quantum theory.